2009
DOI: 10.1200/jco.2008.17.0746
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Cranial Irradiation in Extensive Disease Small-Cell Lung Cancer: Short-Term Health-Related Quality of Life and Patient Reported Symptoms—Results of an International Phase III Randomized Controlled Trial by the EORTC Radiation Oncology and Lung Cancer Groups

Abstract: A B S T R A C T PurposeProphylactic cranial irradiation (PCI) in patients with extensive-disease small-cell lung cancer (ED-SCLC) leads to significantly fewer symptomatic brain metastases and improved survival. Detailed effects of PCI on health-related quality of life (HRQOL) are reported here. Patients and MethodsPatients (age, 18 to 75 years; WHO Յ 2) with ED-SCLC, and any response to chemotherapy, were randomly assigned to either observation or PCI. Health-related quality of life (HRQOL) and patient-reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
172
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(183 citation statements)
references
References 17 publications
5
172
1
5
Order By: Relevance
“…Therefore, patients with complete response to chemotherapy are offered prophylactic cranial irradiation. 24,25 Similarly, patients with SCCB show a risk for the development of brain metastases. Siefker-Radtke et al reported up to 26.7% brain metastases in patients with SCCB.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with complete response to chemotherapy are offered prophylactic cranial irradiation. 24,25 Similarly, patients with SCCB show a risk for the development of brain metastases. Siefker-Radtke et al reported up to 26.7% brain metastases in patients with SCCB.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the main reason for patient refusal to participate in the GawkowskaSuwińska et al study was fear of alopecia. A study of PCI for small cell lung cancer commented that decline in QOL was specifically linked to hair-loss and fatigue (32); therefore if PCI is implemented consideration of hair-loss and fatigue management should be areas of focus. Other late toxicities recorded include mild headache or slight lethargy (22.2%), moderate headache or great lethargy (11.1%) and severe headaches (2.5%) (18).…”
Section: Discussionmentioning
confidence: 99%
“…The QLQ-BN20 has been used to assess QOL in lung cancer patients undergoing prophylactic cranial irradiation [23]. Conducting content validation aims to demonstrate the subjective validity of the questionnaire, as primary brain tumour patients may present with slightly different issues than brain metastases patients.…”
Section: Discussionmentioning
confidence: 99%